Some modifications in transplantation of autologus non -cultured melanocytes-keratinocytes suspension in treatment of segmental and focal vitiligo (Egyptian Experience in Alexandria University) - Nagat Sobhy; Ali Atia; Mahmoud Elramly (Our Dermatology Online, 2013)
Introduction: Transplantation of Autologous non-cultured melanocytes suspension is a simple yet effective cell-based therapy for vitiligo.Materials and Methods: 20 patients with stable vitiligo were subjected to epidermal cell suspension transplantation using Osslon's method with some new modifications.Result: The repigmentation at 7 of the test sites (35.0%) was excellent. It was good for more than half of the test sites (55.0%). Fair repigmentation was encountered among only 2 (10.0%) of the tested sites. None of the tested sites showed poor repigmentation. On the other hand, none of the control sites showed excellent or even good repigmentation. However, repigmentation was fair for nearly 10% and it was poor for 90% of the control sites.Conclusion: Autologus non cultured basal -enriched epidermal cell suspension transplantation is an effective, simple and safe method for treatment of stable vitiligo.